Self-Assessment of Professional Readiness in Graduates of Motor Transport Maintenance and Repair - Elena V. Bogomolova; Sergey A. Fedotov; Maria V. Vasilyeva (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
Self-assessment of professional readiness is an important aspect of professional and personal development in college. It is a complex and multifaceted process. College graduates must critically evaluate their professional experience, knowledge, strengths, prospects, achievements, and failures. They must be able to identify the causes behind their professional disadvantages and develop strategies for improving their professional qualities. A regular self-analysis and reflection help to identify gaps in knowledge and skills, as well as to plan improvement measures. Self-assessment makes it possible to identify the competencies that require the most attention and effort. In addition to technical skills, graduates should possess managerial and digital qualities. Diagnostics of these competencies enables graduates to assess their readiness for independent professional career. This self-assessment online survey involved 84 technical college graduates that majored in Motor Transport Maintenance and Repair (Ryazan). Self-assessment of professional readiness proved to be an important part of professional and supra-professional competencies in graduates of vocational education. The obtained results may help to adjust academic programs, develop methodological materials, and conduct trainings for professional skill development in graduates of technical institutes and colleges.